(untitled) (LEARNing Landscapes, 2023)
Child care and school are similar and interrelated, yet the comparison of school to child care seems contentious. The Covid-19 pandemic revealed pressure points in labeling these educational and care institutions essential—or not. This paper encourages collaboration between schools and child care as a vital component to reimagining education.